2021
DOI: 10.3390/s21020455
|View full text |Cite
|
Sign up to set email alerts
|

Explainable COVID-19 Detection Using Chest CT Scans and Deep Learning

Abstract: This paper explores how well deep learning models trained on chest CT images can diagnose COVID-19 infected people in a fast and automated process. To this end, we adopted advanced deep network architectures and proposed a transfer learning strategy using custom-sized input tailored for each deep architecture to achieve the best performance. We conducted extensive sets of experiments on two CT image datasets, namely, the SARS-CoV-2 CT-scan and the COVID19-CT. The results show superior performances for our mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
137
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(139 citation statements)
references
References 52 publications
(68 reference statements)
2
137
0
Order By: Relevance
“…The underlying framework that enabled this platform to find the best way to train deep learning models has been called Neural Architecture Search (NAS). To achieve the best performance, Alshazly et al [ 19 ] used advanced deep network architecture and suggested a transfer learning strategy that utilized custom-sized input optimized for deep architecture. Silva et al [ 20 ] proposed Efficient CovidNet, a model for detecting COVID-19 patterns in CT images that involves a voting-based approach and cross-dataset analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The underlying framework that enabled this platform to find the best way to train deep learning models has been called Neural Architecture Search (NAS). To achieve the best performance, Alshazly et al [ 19 ] used advanced deep network architecture and suggested a transfer learning strategy that utilized custom-sized input optimized for deep architecture. Silva et al [ 20 ] proposed Efficient CovidNet, a model for detecting COVID-19 patterns in CT images that involves a voting-based approach and cross-dataset analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Machine learning (ML), a form of artificial intelligence, is an emerging alternative that may efficiently develop accurate clinical prediction models that can deal with high-dimensional data, and identify complex relationships between variables and outcomes that may be unidentifiable with traditional statistical approaches [ 11 , 12 , 13 ]. There were several recent breakthroughs demonstrating how using ML to rapidly interrogate complex data delivers a more efficient use of healthcare resources, including the detection of COVID-19 infection by ML interrogation of CT and X-ray images [ 14 , 15 ]. With respect to cancer, there are several ML-based algorithms that can process time-to-event survival outcome data, so identifying a suitable best-performing learning algorithm is critical to developing accurate prediction models of survival.…”
Section: Introductionmentioning
confidence: 99%
“…The healthcare providers are facing intense workload due to the pandemic [8]. To relieve the overwhelming workload, AI systems are being used to detect and identify COVID-19 using medical imaging technologies [9][10][11][12][13][14][15][16][17]. Recent studies on radiology demonstrate promising results on COVID-19 pneumonia classification using chest CTs with the help of deep learning methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…There are different class definition approaches in the COVID-19 related studies like binary or multiclass. Binary classification is usually applied as Covid pneumonia and non-Covid pneumonia [12,17] or Covid positive and Covid negative [14,16]. Multiclass classification separates Covid negative further into Covid pneumonia, non-Covid pneumonia and no pneumonia [9][10][11]13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation